On the domination and signed domination numbers of zero-divisor graph - Ebrahim Vatandoost; Fatemeh Ramezani (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
Let $R$ be a commutative ring (with 1) and let $Z(R)$ be its set of zero-divisors. The zero-divisor graph $Γ(R)$ has vertex set $Z^*(R)=Z(R) \setminus \lbrace0 \rbrace$ and for distinct $x,y \in Z^*(R)$, the vertices $x$ and $y$ are adjacent if and only if $xy=0$. In this paper, we consider the domination number and signed domination number on zero-divisor graph $Γ(R)$ of commutative ring $R$ such that for every $0 ≠ x \in Z^*(R)$, $x^2 ≠ 0$. We characterize $Γ(R)$ whose $γ(Γ(R))+γ(\overline{Γ(R)}) \in \lbrace n+1,n,n-1 \rbrace$, where $|Z^*(R)|=n$.